USE OF DEEP OSCILLATION - THERAPY IN REHABILITATION PROGRAM FOR PATIENT AFTER DISTAL RADIUS FRACTURE WITH A COMPLEX REGIONAL PAIN SYNDROME: A CASE REPORT - G. Мratskova (Trakia Journal of Sciences)
THE PURPOSE is to present a clinical case of a patient with a fracture of the distal radius and complex regional pain syndrome I, in which complex rehabilitation was applied, including Deep Oscillation, cryotherapy and therapeutic exercises. MATERIALS AND METHODS: The rehabilitation program was conducted to a 62-year-old woman, four months after the injury. The intervention includes Deep Oscillation in biphasic mode (up to 7μA) and therapeutic exercises 10 procedures. The clinical symptoms were assessed before and after therapy and after 1-st and 3-rd months after therapy. RESULTS: Reduction in pain (VAS) after therapy from “very strong” (75mm) before therapy, to “mild” at 3 months (12mm) was observed. Reduction of wrist swelling and muscle weakness as assessed by manual muscle testing was observed. The range of movement in the sagittal plane from 25º-0-35º to 70º0º-85º and the frontal plane from 5º-0-15º to 20º-0º-35º was increase. Improved performance of activities of daily living was observed. No adverse events with Deep Oscillation therapy were observed. CONCLUSION: Deep Oscillation and therapeutic exercises effectively reduce the clinical symptoms of regional pain syndrome. To establish the therapeutic efficacy of Deep Oscillation treatment after a fracture of the distal radius with complex regional pain syndrome, randomized studies involving a larger number of patients are required.